Financial Depending and Economic Relations in Indonesia, Malaysia and Singapore - Ni Putu Sintya Dewi; Ni Putu Wiwin Setyari, (MediaTrend, 2022)
A good economy for a country is an ever-increasing economy. The economy of a country can be affected by its financial sector. Economic activity can be encouraged by developments in the financial sector. In this study, the objectives to be achieved are to analyze the effect of the ratio broad money to GDP (M2/GDP), the ratio of domestic credit to the private sector by banks to GDP (PCS/GDP), inflation and the ratio foreign direct investment to GDP (PMA/GDP) simultaneously and partially to the economy (GDP) in Indonesia, Malaysia and Singapore. The approach used is multiple linear regression complete with granger causality test and panel data analysis. The results of the analysis can be seen that partially M2/GDP, PCS/GDP, and PMA/GDP have a positive and significant effect on GDP while inflation has no significant effect on GDP. Simultaneously, these variables have a significant impact on GDP. There is a need for cooperation between the government and banking in accelerating the turnover of money, facilitating credit requirements and maintaining inflation so that it can increase consumption and improve the investment climate.